COMPANY REGULATION DEVELOPMENT ASSISTANCE PT. GLORY CIPTAPRIMA - Jessica Jane; Winda Fitri (Universitas Internasional Batam, 2022)
To run a company, of course you need rules to ensure legal certainty and justice in a company.Company regulations have an important role in a company, where the purpose of the existence of company regulations is to ensure a balance of rights and obligations of each party, as a guide for the parties (employers and workers) to carry out their obligations, ensure justice for the parties, improve welfare workers, as well as creating a harmonious relationship between the parties.The method used in the implementation of this practical work is the empirical method, where the authors make direct observations to obtain the necessary data.